MAP3K1 Variant Causes Hyperactivation of Wnt4/β-Catenin/FOXL2 Signaling Contributing to 46,XY Disorders/Differences of Sex Development - Chen, Hong; Chen, Qingqing; Zhu, Yilin; Yuan, Ke; Li, Huizhu; Zhang, Bingtao; Jia, Zexiao; Zhou, Hui; Fan, Mingjie; Qiu, Yue; Zhuang, Qianqian; Lei, Zhaoying; et al. (Frontiers in Genetics, 2022)
Background: The 46,XY disorders of sex development (46,XY DSD) are rare congenital gonadal dysplasias. During early embryonic development, several genes are involved in strictly regulating the initiation and maintenance of the testicular or ovarian-specific pathways. However, the underlying molecular mechanisms of 46,XY DSD remain elusive. Methods: We ascertained a Chinese DSD pedigree. To assess the history and clinical manifestations for the 46,XY DSD patients, the physical, operational, imageological, pathological, and other examinations were performed for family members. Variant screening was conducted using trio whole-exome sequencing (trio WES) and Sanger sequencing. We constructed transiently transfected testicular teratoma cells (NT2/D1) and ovary-derived granular cells (KGN) , each with mutant or wild-type MAP3K1. A series of functional assays were performed, such as steady-state levels of gender determination related factors, protein interaction, luciferase system and others. Results: Two affected siblings were diagnosed as 46,XY DSD. We identified a missense c.556A>G/p.R186G variant in the MAP3K1 gene. The unique structural disturbance of the MAP3K1R186G variant had altered the local hydrogen bond pattern which may have led to improved local flexibility of the variant. In functional assays MAP3K1R186G showed a significantly decreased affinity to ubiquitin (Ub) of 43~49% and increased affinity to RhoA of 3.19±0.18 times, compared to MAP3K1. MAP3K1R186G caused hyperphosphorylation of p38 and GSK3β and promoted hyperactivation of Wnt4/β-catenin signaling. Increased β-catenin imported into the nucleus then promoted the expression of the pro-ovarian transcription factor FOXL2 gene, which contributed to 46,XY DSD. Conclusion: We identified a missense MAP3K1 variant associated with 46,XY DSD. These findings provide novel insight towards better clinical evaluation and further understanding of the molecular basis of 46,XY DSD.